Diagnostic approach of anemia in ruminants - KATSOGIANNOU, E. G.; ATHANASIOU, L. V.; CHRISTODOULOPOULOS, G.; POLIZOPOULOU, Z. S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Anemia in ruminants is an abnormal condition characterized by the decrease of the hematocrit (Packed Cell Volume, PCV), the mass of erythrocytes (Red Blood Cells, RBCs) and/or hemoglobin. Anemia is classified as hemolytic, hemorrhagic or anemia caused by the decreased production of erythrocytes; the first two categories are characterized by a regenerative response. Hemorrhagic anemia can be caused by ectoparasites or parasites of the gastrointestinal system, hemorrhagic bowel syndrome, abomasal ulcers, vena cava thrombosis as well as from the genitourinary tract. In addition, primary and secondary hemostatic disorders can be accompanied by hemorrhagic anemia. Hemoparasites, toxins produced from Clostridium perfringens type D and Clostridium hemolyticum and leptospirosis are some of the causes of hemolytic anemia. Furthermore, certain plants, drugs or heavy metals and lack of certain trace elements can cause hemolysis. Immune-mediated hemolytic anemia has also been reported in ruminants. The reduced production of erythrocytes can be caused by deficiency of vitamin B12 or iron, as well as by chronic diseases. Pathologic conditions of bone marrow like inflammatory or neoplastic cells filtration and hypoplasia or aplasia of bone marrow are related to reduced production of erythrocytes. After laboratory confirmation by complete blood count analysis, history taking, clinical examination of the animal and specific test depending on the case, are required for the diagnostic approach of anemia and especially for etiological diagnosis. Tachycardia, tachypnea, icterus, mucosal pallor as well as specific symptoms of the underlying disease are observed during the clinical examination of the animal. FAMACHA technique is widely used for the clinical diagnosis and the assessment of the severity of anemia. With respect to complete blood count, apart from the hematocrit, hemoglobin concentration, erythrocytes indices as Mean Corpuscular Volume (MCV) and Mean Corpuscular Hemoglobin Concentration (MCHC) are contributing to the classification of anemia. The size and the shape of the erythrocytes, the appearance of inclusions and reticulocytes, which are indicative of regenerative anemia, are evaluated in blood smear. Rarely, examination of bone marrow is carried out, for the differentiation of anemia as regenerative or non-regenerative. In particular, the confirmation of immune- mediate anemia is based on Coomb’s test for the detection of autoagglutination. Except from hemorrhage, blood loss is detected at urinalysis or feces microscopy for the presence of blood and/or parasites. Finally, serological and molecular techniques for the detection of infectious agents, as well as specific toxicological analysis are performed in various biological materials.